Identification of SYS1 as a Host Factor Required for Shiga Toxin-Mediated Cytotoxicity in Vero Cells - Sakuma, Chisato (Int J Mol Sci, 2021)
Shiga toxin (STx) or Vero toxin is a virulence factor produced by enterohemorrhagic Escherichia coli. The toxin binds to the glycosphingolipid globotriaosylceramide (Gb3) for its entry, and causes cell death by inhibiting ribosome function. Previously, we performed a loss-of-function screen in HeLa cells using a human CRISPR knockout (KO) library and identified various host genes required for STx-induced cell death. To determine whether this library targeted to the human genome is applicable to non-human primate cells and to identify previously unrecognized factors crucial for STx-induced cell death, we herein performed a similar screen in the African green monkey kidney-derived Vero C1008 subline. Many genes relevant to metabolic enzymes and membrane trafficking were enriched, although the number of enriched genes was less than that obtained in the screening for HeLa cells. Of note, several genes that had not been enriched in the previous screening were enriched: one of these genes was SYS1, which encodes a multi-spanning membrane protein in the Golgi apparatus. In SYS1 KO Vero cells, expression of Gb3 and sphingomyelin was decreased, while that of glucosylceramide and lactosylceramide was increased. In addition, loss of SYS1 inhibited the biosynthesis of protein glycans, deformed the Golgi apparatus, and perturbed the localization of trans-Golgi network protein (TGN) 46. These results indicate that the human CRISPR KO library is applicable to Vero cell lines, and SYS1 has a widespread effect on glycan biosynthesis via regulation of intra-Golgi and endosome–TGN retrograde transports.